2011
DOI: 10.1111/j.1399-0012.2011.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D receptor gene polymorphisms on clinical outcomes of HLA‐matched sibling hematopoietic stem cell transplantation

Abstract: We hypothesized that polymorphisms of the vitamin D receptor (VDR) gene might affect clinical outcomes of allogeneic hematopoietic stem cell transplantation (HSCT). Three VDR gene polymorphisms (BsmI G>A, ApaI G>T, and TaqI T>C) were genotyped in 147 patients who underwent HLA-matched sibling allogeneic HSCT. Frequencies of infection, graft-vs.-host disease (GVHD), overall survival (OS), and disease-free survival (DFS) were compared according to genotypes and haplotypes. Infection and acute GVHD had trends to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The functional significance of this allelic variation is unknown and no direct link to high or low VDR activity is reported. This study also found that recipients having two copies of the “A” allele for the Apa I polymorphism experienced decreased rates of acute GVHD and infection [37]. Polymorphisms of Apa I have been correlated to VDR activity with homozygosity for the “a” allele associated with higher VDR activity [4].…”
Section: Vitamin D As a Modulatory Of Immune Response In Allogeneimentioning
confidence: 96%
See 2 more Smart Citations
“…The functional significance of this allelic variation is unknown and no direct link to high or low VDR activity is reported. This study also found that recipients having two copies of the “A” allele for the Apa I polymorphism experienced decreased rates of acute GVHD and infection [37]. Polymorphisms of Apa I have been correlated to VDR activity with homozygosity for the “a” allele associated with higher VDR activity [4].…”
Section: Vitamin D As a Modulatory Of Immune Response In Allogeneimentioning
confidence: 96%
“…They analyzed recipient VDR polymorphisms and retrospectively evaluated the association with patient outcomes including infection, GVHD, overall survival (OS) and disease free survival (DFS) [37]. The most significant findings were a correlation between polymorphisms at the Taq 1 cleavage site where heterozygotes, (those possessing at least one copy of the C allele), had better disease free survival (DFS) and overall survival than TT homozygotes [37]. The functional significance of this allelic variation is unknown and no direct link to high or low VDR activity is reported.…”
Section: Vitamin D As a Modulatory Of Immune Response In Allogeneimentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate gene studies have tested SNP associations with cause-specific (TRM and DRM) and overall survival in redox metabolism genes ( GSTM1 , UGT2B17 ) [ 16 , 17 ] and cytokine and chemokine genes and their receptors ( IL7 receptor-α , IL-10 and TNF-α , IL-1 , IL-1-β , IL-1-α , IL-6 , IL-10 , IL-10R , IL-23 , IL23R , CCL2 , CCR5 , TLR9 ) in both donors and recipients [ 18 30 ]. Other studies focused on variants in genes responsible for immune response and recognition including FCGR3A [ 31 ], CTLA4 [ 23 , 24 , 32 35 ], LCT [ 36 ], and NOD2/CARD15 [ 37 49 ], as well as VDR [ 50 54 ] and MTHFR [ 54 , 55 ] and THBD [ 56 ]. Initial results were promising, reviewed in [ 57 ], and yielded some significant associations with overall survival (OS) and TRM after related and unrelated donor HCT.…”
Section: Overview Of Associations Of Candidate Genes With Survival Afmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The individual contribution from each of these factors and pathways may be challenging to quantify in individual patients; however sophisticated tools and analysis methods are available for assessing the global impact of genetic variation on transplant outcome.…”
Section: Introductionmentioning
confidence: 99%